2017
DOI: 10.1016/j.neuron.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Plasticity, Engrams, and Network Oscillations in Amygdala Circuits for Storage and Retrieval of Emotional Memories

Abstract: The neuronal circuits of the basolateral amygdala (BLA) are crucial for acquisition, consolidation, retrieval, and extinction of associative emotional memories. Synaptic plasticity in BLA neurons is essential for associative emotional learning and is a candidate mechanism through which subsets of BLA neurons (commonly termed "engram") are recruited during learning and reactivated during memory retrieval. In parallel, synchronous oscillations in the theta and gamma bands between the BLA and interconnected struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
196
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(207 citation statements)
references
References 154 publications
(251 reference statements)
8
196
2
1
Order By: Relevance
“…We found that resistant and helpless individuals share electrophysiological markers of stress, but only resistant animals present the neural signature of controllability, in line with Maier and Seligman (2016). Considering that theta oscillations regulate synaptic plasticity and learning (Bocchio et al, 2017;Buzsáki, 2002;Hasselmo and Stern, 2014), theta activity impairments in helplessness could also mean that this syndrome stems from learning deficits rather than a learned response.…”
Section: Theta Impairment and Helplessnessmentioning
confidence: 76%
See 1 more Smart Citation
“…We found that resistant and helpless individuals share electrophysiological markers of stress, but only resistant animals present the neural signature of controllability, in line with Maier and Seligman (2016). Considering that theta oscillations regulate synaptic plasticity and learning (Bocchio et al, 2017;Buzsáki, 2002;Hasselmo and Stern, 2014), theta activity impairments in helplessness could also mean that this syndrome stems from learning deficits rather than a learned response.…”
Section: Theta Impairment and Helplessnessmentioning
confidence: 76%
“…Mounting evidence indicates that theta oscillations have a role in the processing of aversive information (Bocchio et al, 2017;Çalışkan and Stork, 2019;Gray and McNaughton, 2000;Likhtik and Gordon, 2014). Many reports describe increased theta power and synchrony during different stressors, including exposure to distant predators, aggressive conspecifics, anxiogenic environments, and conditioned fear (Adhikari et al, 2010;Hultman et al, 2018;Lesting et al, 2011;Mikulovic et al, 2018;Sainsbury et al, 1987;Seidenbecher et al, 2003).…”
Section: Theta Functions and Stressor Controllabilitymentioning
confidence: 99%
“…Interneuronal networks in the cortex and BNC are important for their contribution to rhythmic oscillations in these regions (Benardo, 1997;Bienvenu et al, 2012;Buzsáki & Chrobak, 1995;Whittington, Traub, & Jefferys, 1995). These interneuronal network rhythms, as well as intrinsic oscillations in BNC PNs (Pape, Paré, & Driesang, 1998), are critical for synaptic plasticity associated with the formation and retrieval of emotional memories (Bocchio, Nabavi, & Capogna, 2017;Pape & Paré, 2010;Paré, Collins, & Pelletier, 2002).…”
Section: Cck+ Neurons In the Monkey Bnc Form An Interconnected Networkmentioning
confidence: 99%
“…With regard to associative emotional learning, it appears that neurons of the basolateral amygdala are recruited during learning, and become reactivated during memory retrieval [60]. …”
Section: Figmentioning
confidence: 99%